The relationship between urban refuse with fecundity and nestlings' success of a generalist seabird in the Río de la Plata Estuary - Uruguay. (December 2021) - Lenzi, Javier; González-Bergonzoni, Iván; Flaherty, Elizabeth; Hernández, Daniel; Machín, Emanuel; Pijanowski, Bryan
Abstract: Resource acquisition and allocation impacts individual fitness. Using pellet analysis of breeding adults and stable isotopes of carbon and nitrogen of down feathers of Kelp Gull ( Larus dominicanus ) nestlings, we evaluated the relationship between urban refuse (beef and chicken) and natural food (fish) consumption of individual females during the pre-incubation period, with fecundity and young nesting's success in the Río de la Plata Estuary in Uruguay. Assimilated urban refuse positively correlated with egg weight and negatively with young nestling's success. This suggests a possible impact of urban refuse foraged by females during the pre-incubation period on their immediate fecundity (positively) and young nestling's survival (negatively). Differences between studies at the individual and colony levels are also discussed in light of an "ecological fallacy" of interpretation and we thus argue for the need of additional research to evaluate this relationship further, considering potential confounding factors. Graphical abstract: Unlabelled Image Highlights: Fitness consequences of Kelp Gull females that forage on refuse were studied. Urban refuse consumption positively correlated with egg weight. Urban refuse consumption negatively correlated with young nestling's success. Fish consumption negatively correlated with egg weight. Fish consumption positively correlated with young nestling's success.